2016
DOI: 10.7150/ijms.16642
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of BDNF, GNB3, MTHFR, ACE and APOE Variants in Major and Recurrent Depressive Disorders in Russia

Abstract: This study was conducted to explore the possibility of association between the single-nucleotide polymorphisms rs6264 of BDNF, rs5443 of GNB3, and rs1801133 of MTHFR; the In/Del polymorphism of ACE; and the ε2 allele of APOE and major depressive disorder (MDD) and recurrent depressive disorder (RDD) in an East Slavic population. Generalized multifactor dimensionality reduction (GMDR) method was applied to detect gene-gene interactions. One hundred fifty patients with RDD (101 females and 49 males) and 208 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Although miR-124 has been widely studied in animal models of depression, few studies have investigated the relationship between the levels of miR-124 and Mdd in clinics. Recent studies have reported that miR-124-3p was upregulated in the BA46 area of the brain (44) and in peripheral blood mononuclear cells in patients with Mdd (45). miR-124 expression levels were also increased in the hippocampus of rat models of depression (46,47).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although miR-124 has been widely studied in animal models of depression, few studies have investigated the relationship between the levels of miR-124 and Mdd in clinics. Recent studies have reported that miR-124-3p was upregulated in the BA46 area of the brain (44) and in peripheral blood mononuclear cells in patients with Mdd (45). miR-124 expression levels were also increased in the hippocampus of rat models of depression (46,47).…”
Section: Discussionmentioning
confidence: 96%
“…These results revealed that miR-124-3p may regulate the mTOR signaling pathway by reducing the expression of ddIT4, which stabilizes the complex formed by TSc1 and TSc2; this complex subsequently inhibits mTORc1-dependent protein synthesis and cell growth (50). Research has demonstrated that miR-124-3p was correlated with cell growth, proliferation and apoptosis, as well as the mTOR pathway (45). diagnostically, Mdd is associated with smaller regional brain volumes (53).…”
Section: Discussionmentioning
confidence: 99%
“…[9–12] A large number of epidemiological studies have investigated the relationship between the C677T polymorphism of MTHFR and many diseases, including breast cancer, colorectal cancer, ischemic stroke, depressive disorders, and hypertension. [1317]…”
Section: Introductionmentioning
confidence: 99%
“…The SNP and VNTR genotyping was carried out using locus-speci c PCR as described previously [40][41][42][43][44][45].…”
Section: Dna Isolation and Genotypingmentioning
confidence: 99%